Groundwater Game, a water game app around sustainable water resource use for farming in India - CGIAR Platform for Big Data in Agriculture (2019)
The game was developed and deployed on the Kalgudi platform with some 600,000 farmers and will be used at larger scale in a real watershed somewhere. Key user testing was done with 100 concurrent users at the Big Data Convention, getting this game ready for use in the wider world.